Estudio del perfil de la demanda turística del Cantón Esmeraldas, Provincia Esmeraldas, año 2021 - Acosta Vásquez, María Emilia (2021)
The purpose of this research is to contribute with important information on the current tourism demand of the canton of Esmeraldas with the purpose of reactivating tourism in the canton, province and country. We worked with three objectives, and for its fulfillment, which were the design, application and definition. We proceeded with the application of surveys to the study population whose value was to obtain the demographic, economic, motivational and preference variables, in order to obtain the results obtained through the descriptive study by means of the interpretation of data and the qualitative method and the validation with a judgment of experts, thus taking the data to carry out the descriptive and inferential statistics. Concluding with the estimation of the profile of the tourist demand of the canton of Esmeraldas based on the compliance of 385 tourists surveyed for what was found to be a demand of variably young tourists with influence of male gender with 58.7% and under 34 years of age, with a favorable income greater than $400 dollars, with great interest in exploring new attractions and disconnecting from the everyday. In terms of nationality, it was estimated that tourists are mostly nationals from the highlands. As a point of motivation generated by the canton, the majority of respondents allude to relaxation with more than 95%, which means that the city is a chosen point to get away from everyday life, enjoy its tourist beauties and the gastronomic tourism of the canton. So that the canton of Esmeraldas can aim towards tourism development with the objective of the demand of tourism personnel, it is decided to allow the project to serve as a basis for the design of new projects